Integration of Tolkama Media in the Problem Based Learning (PBL) Model to Improve Understanding of the Concept of Multiplication in Elementary Schools - Zakiyah, Yumi; Setyaningsih, Nining; Qudriyati, Ari; Murtiasa, Budi (Universitas Negeri Makassar, 2025)
This study aims to analyze the effect of integrating Tolkama media (mathematical multiplication bottles) into the Problem Based Learning (PBL) model on elementary school students’ understanding of multiplication concepts. A quantitative approach with a pre-experimental One-Group Pretest–Posttest design was employed to assess students’ learning improvement. The research subjects consisted of 31 third-grade students at SD Birrul Walidain Muhammadiyah Sragen. Data were collected through pretest and posttest instruments covering indicators of understanding multiplication as repeated addition, equal groups, solving simple problems, and applying concepts in contextual situations. Data analysis included the Shapiro-Wilk normality test, Paired Sample t-Test, and N-Gain calculation. The results indicated an increase in the average score from 67.74 in the pretest to 81.94 in the posttest, with t = −16.304 and Sig. (2-tailed) = 0.000, demonstrating a statistically significant improvement. The N-Gain value of 0.5082 indicates a moderate level of conceptual understanding enhancement. These findings confirm that integrating Tolkama media within the PBL model effectively supports students in constructing meaningful understanding of multiplication concepts. This study provides practical implications for teachers in designing problem-based learning with concrete media support.